Rapid high throughput template preparation (rHTTP) method: a novel cost effective method of direct PCR for a wide range of plants - Prassan Choudhary; Sudipta Das; Hillol Chakdar; Arjun Singh; Sanjay Kumar Goswami; Anil Kumar Saxena (BMC Biotechnology, 2019)
Abstract Background Conventional plant DNA isolation methods are complex, time consuming and require technical expertise. These limitations were overcome using the DNA isolation kits which, however significantly add to the research costs. Hence the present study was aimed to develop a high throughput, rapid and inexpensive method of PCR ready DNA template preparation from plant materials. Methods Concentration of SDS in lysis buffer, amount of starting material, period and temperature for lysis were optimized for obtaining PCR ready templates from plant materials. The method was tested using RAPD and ITS specific primers for different plant species like rice, wheat, mustard, pea, soybean, pigeonpea, tomato, maize, march lilly, bougainvillea, Indian blanket flower, nerium, petunia, purple pirouette petunia, moses-in-the-cradle, golden cane palm, duranta, periwinkle, chrysanthemum and two xerophytes viz. Dipterygium glaucum and Crotaleria burhia. SSR markers RM18398 and RM26108 showed successful amplification in rice varieties Improved Pusa Basmati 1 and KS Dev 12. The effectiveness of the method was tested using fresh as well as 1 year old tissues. The storability of the lysate was also tested. Results In this report, we developed a novel method called rapid high throughput template preparation (rHTTP) method to prepare PCR ready DNA templates. Most striking feature of this technique is that it can be done anywhere where water can be boiled by any means. Using rHTTP method, PCR ready templates can be prepared in just 10 min. Robust and reproducible amplification for all the test plants were recorded with RAPD, plant ITS primers and SSR markers following this method. rHTTP methods works well for both fresh as well as old plant tissues. The lysates had a shelf life of 1 month when stored at 4 °C and 3 days when stored at room temperature. Conclusions rHTTP method has several advantages over the other protocols like ease of execution, no requirement of tissue grinding/liquid nitrogen/hazardous chemicals and above all, equally effective for both fresh and old samples. Using this method, costs per prep comes down ~ 10–50 times as compared to most commercial kits. This method can be used for on-field experiments like molecular diagnostics, varietal identification etc.